Implementasi Prinsip Good Corporate Governance di Divisi Sumber Daya Manusia Pada PT Pertamina Pusat - Dwi Pratiwi, Windi; Gandini Purbaningrum, Dini (PUBLICNESS: Journal of Public Administration Studies, 2023)
Peruvian Governance Good Corporate Governance is basically an effort to make GCG a rule and guideline for Company managers in carrying out their business activities. The purpose of this study is to find out, analyze and describe the implementation of the principles of Good Corporate Governance at PT Pertamina (Persero). This research uses a qualitative approach with a descriptive method. The method of data collection is carried out by interviews, observations and documentation. The theory used in this study uses the theory of the basic principles of Good Corporate Governance in Hamdani's book (Review of Ethics in Business Practice), namely the principles of transparency, accountability, responsibility, independency and Fairness. The results of this study show that the implementation of the principles of good corporate governance has been implemented by PT Pertamina Persero properly even though it has not been maximized. This is evidenced by transparency with the existence of an official website that can be accessed at any time, as well as clarity in decision making, annual reports, financial reports, and recruitment processes.